Characterization of industrial Pt-Sn/Al2 O3 catalyst and transient product formations during propane dehydrogenation - Ho, Kah Sing; Chye, Joanna Jo Ean; Chin, S. Y.; Cheng, C. K. (Department of Chemical Engineering, Diponegoro University, 2013)
The major problem plaguing propane dehydrogenation process is the coke formation on the Pt-Sn/Al2O3cat-alyst which leads to catalyst deactivation. Due to information paucity, the physicochemical characteristics of the commercially obtained regenerated Pt-Sn/Al2O3catalyst (operated in moving bed reactor) and coke formation at different temperatures of reaction were discussed. The physicochemical characterization of re-generated catalyst gave a BET surface area of 104.0 m2/g with graphitic carbon content of 8.0% indicative of incomplete carbon gasification during the industrial propylene production. Effect of temperatures on coke formation was identified by studying the product yield via temperature-programmed reaction carried out at 500 oC, 600 oC and 700 oC. It was found that ethylene was precursor to carbon laydown while propylene tends to crack into methane. Post reaction, the spent catalyst possessed relatively lower surface area and pore radius whilst exhibited higher carbon content (31.80% at 700 oC) compared to the regenerated cata-lyst. Significantly, current studies also found that higher reaction temperatures favoured the coke for-mation. Consequently, the propylene yield has decreased with reaction temperature.